Pendampingan Pembuatan Pewarnaan Tekstil Shibori Sebagai Upaya Menciptakan Produk Ekonomi Kreatif Agen Wanita Desa Batursari - Angga Septiyanto; Istna Syaikhah Hanun; Rahma Aprilia; Azzahra Tribuana Alim (Jurnal Bina Desa, 2026)
In the world of textiles, there are various types of motifs on fabrics that come from traditions and typical coloring techniques in each culture, each of which contains certain meanings and uniqueness. This service activity aims to improve the skills and creativity of women agents in Batursari Village in making textiles with Shibori dyeing techniques. Through this assistance, the participants were given training ranging from the introduction of basic techniques to direct practice of making Shibori textiles with methods including lectures, demonstrations, and practices. The Shibori dyeing technique has great potential as a creative economic product, especially in the context of empowering women in Batursari Village. The results of this activity showed an increase in participants' skills and creativity in producing Shibori textile products that have high selling value. In addition, this activity also succeeded in raising participants' awareness of the potential of the creative economy that can be developed in their village.